Libya : Technical Assistance Report-Review the Installation/Implementation Status of Modules/Functionalities of ASYCUDA World at Libyan Customs Administration. (IMF Staff Country Reports; Country Report, 2022)
Middle East Technical Assistance Center (METAC) has arranged a two-phase capacity development (CD) for the Libyan Customs Administration (LCA) of the Libyan Ministry of Finance. The purpose of this mission is to assess the development status of the ASYCUDA World (AW) prototype piloted in the Port of Tripoli and identify areas of short-term CD support enabling LCA to fully exploit the AW functionalities. It will be followed by a study tour to promote peer learning and exchange of best practices in the f ield of customs in particular digitalization issues, through the METAC region.